CLASS STRUGGLE AGAINTS HUMAN’S OPPRESSION IN JAMES CAMERON’S AVATAR (2009): A MARXIST APPROACH - ARIANTO, PUPUT (2011)
The major problem of this study is to reveal how the class struggle is reflected in James Cameron’s Avatar movie viewed by Marxist perspective. The objective of this study is to analyze the movie based on its structural elements and a Marxist approach. In analysis, the writer uses qualitative method. The object of the study is James Cameron’s Avatar released in 2009 in the United States. The data sources consist of primary and secondary data sources. The primary data source is Avatar movie itself and the secondary data sources are the other sources related to the primary data such as the information taken from internet, websites, and the historical background of American in the early of twenty first century. The method of the data collection are watching the movie, taking notes the important data, capturing image from the movie, classifying the data into categories and the last is drawing conclusion to get the last result. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusion. First, based on the structural analysis, James Cameron wants to deliver a message that every human is created equal, there is no one allowed to disturb another right. Second, based on the Marxist analysis, James Cameron reflects the racial discrimination by present Marxist issues in this movie. The Na’vi struggle against the oppression to seeking the freedom for life and living which is begun by several conflicts.